2015
DOI: 10.1111/nph.13785
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term nitrogen deposition linked to reduced water use efficiency in forests with low phosphorus availability

Abstract: SummaryThe impact of long-term nitrogen (N) deposition is under-studied in phosphorus (P)-limited subtropical forests. We exploited historically collected herbarium specimens to investigate potential physiological responses of trees in three subtropical forests representing an urbanto-rural gradient, across which N deposition has probably varied over the past six decades. We measured foliar [N]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 96 publications
4
70
1
1
Order By: Relevance
“…A study in subtropical China reported that plant N:P ratios were greater in evergreen broadleaved forest when compared to needle‐leaf and mixed forests (Huang et al., ). The significant increases observed in C:P and N:P ratios in subtropical broadleaf forest soils, together with the results from recent studies reporting N deposition‐associated increases in leaf N:P ratios in three subtropical forests during the past six decades (Han et al., ; Huang et al., ; Li et al., ), suggest that evergreen broadleaved forest (the most typical natural vegetation type) in subtropical China has experienced aggravated P limitation as compared to other vegetation types.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A study in subtropical China reported that plant N:P ratios were greater in evergreen broadleaved forest when compared to needle‐leaf and mixed forests (Huang et al., ). The significant increases observed in C:P and N:P ratios in subtropical broadleaf forest soils, together with the results from recent studies reporting N deposition‐associated increases in leaf N:P ratios in three subtropical forests during the past six decades (Han et al., ; Huang et al., ; Li et al., ), suggest that evergreen broadleaved forest (the most typical natural vegetation type) in subtropical China has experienced aggravated P limitation as compared to other vegetation types.…”
Section: Discussionmentioning
confidence: 60%
“…Subtropical and tropical soils are usually strongly weathered and have low total P content and availability (Vitousek et al, 2010;Walker & Syers, 1976;Zhang et al, 2005). Previous studies from China suggested that soil P likely limits primary production in subtropical regions (Han, Fang, Guo, & Zhang, 2005;Huang et al, 2015;Zhang et al, 2005). A recent meta-analysis of P additions combined with N enrichment concluded that P limitation is likely to become more severe under continued or increasing N deposition (Li, Niu, & Yu, 2016).…”
mentioning
confidence: 99%
“…As a critical link between ecosystem production and resource supply in terrestrial ecosystems, resource use efficiencies (RUEs), the ratio of carbon assimilation to the captured resource supply, have been widely used to understand ecosystem response to climate change and extremes (Huang et al, 2016;Limousin et al, 2015). RUEs are important controlling factors in many ecosystem production models (Garbulsky et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change projections are forecasting increasing atmospheric CO 2 concentrations, warmer temperatures, more variable precipitation, and frequent extreme climate events in the future (IPCC, 2014). These changes are expected to profoundly impact the ecosystem's supply of photosynthetic resources (i.e., light, carbon [CO 2 ], and water; Chen et al, 2015;Limousin, Yepez, McDowell, & Pockman, 2015) and also the functional plant structure (Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation